Konsumsi Jamu dengan Kandungan Kortikosteroid terhadap Kejadian Hipertensi Sistolik - Roni Trisnawan; Sutanto Priyo Hastono (Universitas Faletehan, 2023)
One of the risk factors of hypertension is drugs consumption. Meanwhile, in general population there are still many people who consume herbs which surprisingly contain a lot of medicinal chemicals (prednisone, dexamethasone, phenylbutazone) which are believed to have an effect on blood pressure. The purpose of this study was to determine the relationship between consumption of herbs and corticosteroids in the incidence of systolic hypertension among visitors of public health center aged > 18 years. The research method used an observational design and a cross-sectional study design. The research used primary data obtained by interview and measurement technique and secondary data obtained from medical record. The research was conducted in December 2022 at Cigudeg Public Health Center, Bogor Regency. The sampling technique used simple random sampling, obtained 70 respondents with criteria of complete medical record data and > 18 years old. The research results showed that 58.6% of respondents had hypertension, 24.3% consumed herbs containing corticosteroids, 82.4% of the group who consumed herbs containing corticosteroids experienced hypertension, and 17.6% of them did not experience hypertension. The use of herbs containing corticosteroids had an impact on increasing hypertension in respondents.